2011
DOI: 10.2169/internalmedicine.50.6113
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Tumor Thrombotic Microangiopathy Associated with Esophageal Squamous Cell Carcinoma

Abstract: Pulmonary tumor thrombotic microangiopathy (PTTM) is an uncommon cancer-related complication that has been most frequently reported to be associated with adenocarcinoma. We present a case of PTTM which developed in a 60-year-old man with esophageal carcinoma. One year after definitive treatment of the tumor, he developed pulmonary hypertension. Transbronchial lung biopsy (TBLB) specimens showed fibrocellular intimal proliferation and luminal stenosis of the small pulmonary vessels, which contained squamous cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…Based on this suspicion, we treated the patient with S-1 and cisplatin as first line and with S-1 and gemcitabine as second line therapy. Ours is the third case reported in English in which the diagnosis of PTTM was made while the patient was alive (2,9), and this case is the first report in which combination chemotherapy achieved a therapeutic effect.…”
Section: Discussionmentioning
confidence: 72%
“…Based on this suspicion, we treated the patient with S-1 and cisplatin as first line and with S-1 and gemcitabine as second line therapy. Ours is the third case reported in English in which the diagnosis of PTTM was made while the patient was alive (2,9), and this case is the first report in which combination chemotherapy achieved a therapeutic effect.…”
Section: Discussionmentioning
confidence: 72%
“…Various malignancies from different site of origin including esophageal squamous cell carcinoma, ovarian tumors, desmoplastic small cell tumor, salivary duct carcinoma ex pleomorphic adenoma and pulmonary adenocarcinoma were also reported in literature associated with PTTM [4][5][6][7][8][9][10].…”
Section: Review Of Literature and Discussionmentioning
confidence: 99%
“…During review of literature, we found 10 patients having antemortem diagnosis of PTTM [4,17,18,27]. The primary site of tumor was upper gastrointestinal tract in 4 of them, breasts in 3 of them, unknown in two of them, and lungs in one of them.…”
Section: Review Of Literature and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional pulmonary angiography may show occlusion of distal vessels but without abrupt narrowing or intravascular webs suggestive of chronic thromboembolic pulmonary hypertension [5]. High-resolution computed tomography findings are non-specific but may demonstrate ground glass opacification, mosaicism (reflecting small vessel occlusion) [5], small pulmonary nodules (due to fibrointimal thickening), diffuse shadows [6], consolidation, tree-in-bud [7] and interlobular septal thickening (when pulmonary vein or lymphatics are involved). Interestingly, the recent European Society of Cardiology/European Respiratory Society pulmonary hypertension guidelines suggest that computed tomography is useful in many respects, but does not emphasis the potential role for computed tomography (and/or ultrasound) of the abdomen and pelvis to assess for malignancy [8].…”
Section: From the Authorsmentioning
confidence: 99%